Dakwah Siber dan Pergeseran Religiusitas Masyarakat Kenjeran Surabaya - Maulidatus Syahrotin Naqqiyah; Zidni Ilman Nafi’a; Agoes Moh. Moefad; Ahmad Bajuri (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2022)
The emergence of high advanced communication and information technology has shifted the socio-religious traditions and values. This study attempts to describe the shifting of religious behaviour and values within the coastal society of Kenjeran, Surabaya City as the implications of new media intervention and the rise of cyber-based da'wah. Using a descriptive qualitative method, the results of the study show that the development of the internet and cyber da'wah has changed how Kenjeran community practices and comprehends religious values and rituals currently; first, there has been the fragmentation within Kenjeran Muslim society's religious teachings and ideology down to the family level; second, there has been a degradation of sacred values in socio-religious activities; third, the way people studying religion tend to ignore the importance of sanad (chain of transmission), which is regarded not relevant with Islamic teachings or ethics.